EXOSKELETON SPRING ASSISTED SUPPORT FOR LABORS AND ARTHRITIS PATIENTS - PRATIKSHA P. GURAV; KISHOR M. WAGHMARE; SHUBHAM S. MHAMANE (International Journal of Innovations in Engineering Research and Technology, 2021)
The labours working in production industry, restaurants, assembly work they will get tired after couple of hours. Standing for many hours causes muscular pain and leads to increase the body stress. As like this, the people suffering from the knee disorders such as “Arthritis” have to sit where they needed. For that reason concept of comfortable support is introduced. In previous researches for this concept pneumatic support and hydraulic system were used. In this project we are replacing pneumatic support and hydraulic system by spring support and mechanical linkages; such that it will reduce the cost and weight of thesupport.This support will help to increase the human health and comfort. It will allow the patients of “Arthritis” to sit and get up easily. We will also work to make it economical.